Study of High Yielding Varieties Programme— 1968-69 Design, Schedules etc. and Instructions—Annexure - Planning Commission (Planning Commission, 1968)
This compendium is only an Annexure to the one prepared last year and contains the revisions etc. effected in this year's study of the High Yielding Varieties Programme. It may please be noted that there are certain changes in the main objectives of the Study on account of which certain additional items of information need to be collected. For instance, the guide points for the research station seek to collect information on the progress of research on the high yielding varieties and the problems there of Similarly, on the cost of cultivation certain additional items have been included in the respondent schedule. It is also proposed to collect field information on some of the important aspects of the programme such as soil testing, recommended practices at the block and respondent levels.
Programme Evaluation Organisation Planning Commission Government of India